2015
DOI: 10.1158/1078-0432.ccr-15-0126
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways: Fatty Acid Synthase

Abstract: Therapies that target tumor metabolism represent a new horizon in anticancer therapies. In particular, cancer cells are dependent on the generation of lipids, which are essential for cell membrane synthesis, modification of proteins, and localization of many oncogenic signal transduction enzymes. Because fatty acids are the building blocks of these important lipids, fatty acid synthase (FASN) emerges as a unique oncologic target. FASN inhibitors are being studied preclinically and beginning to transition to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
193
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(199 citation statements)
references
References 43 publications
2
193
0
4
Order By: Relevance
“…21 As a major enzyme in lipogenesis, FASN has been the main target for developing small molecule inhibitors. 46,47 Virtually all these small molecules inhibit b-ketoacyle-reductase, which is critical for FASN's enzymatic activity. A complete list of FASN inhibitors can be found in a recent review.…”
Section: Fasn Is Required For Akt and Akt/c-met Driven Hepatocarcinogmentioning
confidence: 99%
“…21 As a major enzyme in lipogenesis, FASN has been the main target for developing small molecule inhibitors. 46,47 Virtually all these small molecules inhibit b-ketoacyle-reductase, which is critical for FASN's enzymatic activity. A complete list of FASN inhibitors can be found in a recent review.…”
Section: Fasn Is Required For Akt and Akt/c-met Driven Hepatocarcinogmentioning
confidence: 99%
“…In cancer, however, cells overexpress FASN enzyme to synthesize almost all their fatty acids de novo (14,16). We and others have shown that blocking FASN activity has anticancer activity via the apoptotic pathway in vitro and in vivo (17)(18)(19), by disrupting lipid membrane synthesis and modification of protein palmitoylation and deregulating oncogenic signaling pathways (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Tumour cells present a typical phenotype of abnormally elevated fatty acid synthase (FAS) activity, which indicates that this enzyme is a good target for treating some malignancies [1,2]. FAS catalyses fatty acid synthesis from the substrates acetylCoA and malonyl-CoA [3].…”
Section: Introductionmentioning
confidence: 99%